Differential effects of atmospheric cues on emotions and loyalty intention with respect to age under online/offline environment - Loureiro, S. M. C.; Roschk, H. (Journal of Retailing and Consumer Services, 2014)
Effects of atmospheric cues are usually not compared across offline and online contexts as well as across age groups. This study proposes a model that examines the effect of the atmospheric cues graphics design and information design on positive emotions and loyalty intentions. The model is compared across offline and online stores and regards the consumers' age as moderator. A field study was conducted, which collected data from 363 customers. Hypotheses are tested using structural equation modeling. Results for the offline context reveal that graphics design foster positive emotions and loyalty. Information design predicts loyalty. Results for the online context reveal that information design is salient over graphics design. Information design fosters positive emotions and loyalty, while graphics design does not. Further, we found that in the offline context positive emotions predict loyalty among younger customers but not among older ones. In the online context the effect of graphics design on loyalty is stronger and, thus, significant for younger customers than compared to older ones.